Combined Diagnostic Workflow for Lymphadenopathy: Correlation Between FNAC, Culture, Histopathology, Peripheral Blood Findings, Microbiological Analysis with Inclusion of Pediatric and Genetic Considerations - Bushra Adeel, Nazia Akber Mir, Huma Aslam, Sonia Tahir, Zubaria Rafique, Maimoona Aslam (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Lymphadenopathy encompasses diverse etiologies, including infectious, neoplastic, autoimmune,and genetic disorders. This prospective cross-sectional study assessed a combined diagnosticworkflow—including fine-needle aspiration cytology (FNAC), microbial cultures, histopathology,